2019
DOI: 10.18502/kss.v3i19.4892
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook in EFL Writing Class: Its Effectiveness from Students’ Perspective

Abstract: Social media has now much been integrated as a learning platform in various educational settings, including those in Language Teaching and Learning (LTL). Increasing number of studies has also reported the effectiveness of social media to support LTL activities. This present study aimed to investigate whether Facebook, as the most popular social media in Indonesia, would be an effective learning tool for EFL university students taking advanced writing class. This study employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 9 publications
5
41
0
Order By: Relevance
“…The high rates given to pedagogical features such as motivation, collaboration, communication, interaction, and building up a good rapport with peers confirm the Facebook educational advantages. This aligns with previous studies (e.g., Greenhow and Robeli, 2009b;Ghani, 2015;Hew, 2011;Fithriani et al, 2019;Selwyn, 2007). that recommended Facebook integration in formal classroom learning.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 93%
“…The high rates given to pedagogical features such as motivation, collaboration, communication, interaction, and building up a good rapport with peers confirm the Facebook educational advantages. This aligns with previous studies (e.g., Greenhow and Robeli, 2009b;Ghani, 2015;Hew, 2011;Fithriani et al, 2019;Selwyn, 2007). that recommended Facebook integration in formal classroom learning.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 93%
“…Based on the data from Statista [20], as of the second quarter of 2020, Facebook is the biggest social network worldwide, with over 2.7 billion monthly active users. Studies have shown positive impacts of the Facebook app as a potential tool for the teaching and learning process [21] [22] [23] [24]. According to our findings, the ranking as the most used SNS indicates that Facebook has great potential to be used as a tool for teaching and learning.…”
Section: Regression Modelmentioning
confidence: 55%
“…According to our findings, the ranking as the most used SNS indicates that Facebook has great potential to be used as a tool for teaching and learning. Facebook's popularity worldwide could also be considered a potential to be integrated into teaching and learning as it provides its users with the opportunity to interact with people of different mother tongues and countries of origin [24]. Thus, Facebook will be a useful tool for learning in the future.…”
Section: Regression Modelmentioning
confidence: 99%
“…However, they mostly investigated its use as an outside class activity or a voluntary activity (see Jin, 2015;Kabilan et al, 2010;Kasuma & Tan, 2019;Rodliyah, 2016;Rubrico & Hashim, 2014). Some others were in teaching writing contexts (see Bani-Hani et al, 2014;Fithriani et al, 2019;Miftah, 2016;Putri, 2018;Rodliyah, 2016;Sakkir & Dollah, 2019), and grammar (see Sumakul, 2012). Meanwhile, Abusa'aleek (2015) and Salih and Elsaid (2018) investigated the participants' perceptions and attitudes of using Facebook as an EFL e-learning environment.…”
Section: Introductionmentioning
confidence: 99%